"It Is My Destiny as a Woman": On Becoming a New Mother in Indonesia. (November 2015) - Afiyanti, Yati; Solberg, Shirley M.
Purpose: The purpose of the study was to provide a greater understanding of the experience of the new Indonesian mother.Design: This study was a hermeneutic phenomenological study. Data were obtained from 13 first time Indonesian mothers through semi-structured interviews.Findings: Two main themes were identified: "trying to be a good mother " and "confirming my destiny as a woman." A number of subthemes were identified to understand of how women in rural West Java perceived the meaning of being a new mother. These themes and subthemes described the woman's responsibilities as a new mother and some of the challenges that she accepted as a part of her destiny.Conclusion: This study provides nurses and others with insights into the experiences of Indonesian women with early motherhood, their feelings about taking on the mothering role, and some of their needs during this period.